Lungenkarzinomscreening mit Röntgenthorax oder CT: aktuelle Datenlage = Lung cancer screening with thoracic X‑ray and CT : current situation - Stackelberg, Oyunbileg von; Kauczor, Hans-Ulrich (Der Radiologe, 2016)
Clinical/methodical issueAttempts at the early detection of lung cancer using imaging methods began as far back as the 1950s.Standard radiological methodsSeveral studies attempted to demonstrate a reduction of lung cancer mortality by chest radiography screening but all were unsuccessful.Methodical innovationsEven the first small screening studies using computed tomography (CT) could not demonstrate a reduction in lung cancer-specific mortality until in 2011 the results of the largest randomized controlled low-dose CT screening study in the USA (NLST) were published. The NLST results could show a significant 20 % reduction of lung cancer mortality in elderly and heavy smokers using CT.PerformanceConfirmation of the NLST results are urgently needed so that the data of the largest European study (NELSON) are eagerly awaited.AchievementsPooled with the data from several smaller European studies these results will provide important information and evidence for the establishment of future CT screening programs in Europe.Practical recommendationsRandomized controlled trials are the basis of evidence-based medicine; therefore, the positive results of the methodologically very good NLST study cannot be ignored, even if it is the only such study completed so far with highly convincing conclusions. The NLST results clearly demonstrate that positive effects for the health of the population can only be expected if the processes are clearly defined and the quality is assured.
Gesehen am 11.01.2018